2018
DOI: 10.1186/s12917-018-1513-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with polyphenols on meat quality in Saanen goat kids

Abstract: BackgroundDiet supplementation with polyphenols is a novel strategy to improve meat quality in livestock, by preventing oxidative deterioration of lipids and protein. Polyphenols have beneficial effects on both human and animal health and can be obtained from several sources, such as olive mill wastewaters (OMWW). These are severe environmental pollutants and therefore may be recycled and utilized in other sectors. The aim of this study was to evaluate growth performance, meat characteristics, fatty acid compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 62 publications
1
54
0
Order By: Relevance
“…Goat kids fed with 3.2 mg/day of polyphenols powder extract obtained from Olive mill wastewaters produced meat characterized by a significant reduction of short and saturated fatty acids. Furthermore, a higher (p < 0.05) proportion of monounsaturated fatty acids was recorded in the treated group with a concomitant lower (p < 0.05) MDA formation in the treatment group compared to control group, and no effects were recorded on PUFA [119]. As reported by authors the acidic composition of meat in ruminants is generally different from that of non-ruminants.…”
Section: Ruminantsmentioning
confidence: 48%
“…Goat kids fed with 3.2 mg/day of polyphenols powder extract obtained from Olive mill wastewaters produced meat characterized by a significant reduction of short and saturated fatty acids. Furthermore, a higher (p < 0.05) proportion of monounsaturated fatty acids was recorded in the treated group with a concomitant lower (p < 0.05) MDA formation in the treatment group compared to control group, and no effects were recorded on PUFA [119]. As reported by authors the acidic composition of meat in ruminants is generally different from that of non-ruminants.…”
Section: Ruminantsmentioning
confidence: 48%
“…This evidence has drawn the attention of clinicians and animal scientists to the possibility of turning animal-derived products into functional foods providing health benefits to consumers [3537]. Studies have reported that the content of n -3 PUFA in swine muscle can be increased adding oilseed ingredients to the feed [38,39], and the addition of antioxidant compounds such as vitamin E and polyphenols can help to avoid lipid oxidation [38,40]. Anyway, the knowledge on the muscle physiological processes influenced by dietary antioxidant addition is still poor and could involve a large number of genes associated with both muscle metabolism and structure [41].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, MDA has been evaluated as an oxidative stress diagnostic biomarker in diabetes (Yatoo et al, 2016; Ma et al, 2018), ketosis, ovarian cyst, mastitis and lameness (Kapusta et al, 2018). Its elevated concentration in milk and meat has shown deleterious effects on milk (Yatoo et al, 2015; Kapusta et al, 2018), and meat (Cimmino et al, 2018) quality and hence can serve as a quality biomarker in foods.…”
Section: Types Of Biomarkersmentioning
confidence: 99%